Association of Liver Fibrosis With Cardiovascular Diseases in the General Population: The Multi-Ethnic Study of Atherosclerosis (MESA). (March 2018) - Ostovaneh, Mohammad R.; Ambale-Venkatesh, Bharath; Fuji, Tomoki; Bakhshi, Hooman; Shah, Ravi; Murthy, Venkatesh L.; Tracy, Russell P.; Guallar, Eliseo; Wu, Colin O.; Bluemke, David A.; Lima, João A.C.
Abstract : Background—: The association of cardiovascular diseases (CVD) with liver fibrosis is poorly understood. We aim to assess the association of liver fibrosis by T1-mapping magnetic resonance imaging and CVD in MESA (Multi-Ethnic Study of Atherosclerosis). Methods and Results—: MESA enrolled 6814 participants free of clinical CVD at baseline (2000–2002). A subsample of participants underwent T1-mapping magnetic resonance imaging 10 years after the baseline (Y10 MESA exam, 2010–2012). Liver T1 maps were generated avoiding vessels and biliary ducts from which native T1 (n=2087) and extracellular volume fraction (ECV, n=1234) were determined. Higher ECV and native T1 were indicators of liver fibrosis. Linear regression analysis evaluated the cross-sectional relationship between liver native T1 and ECV at Y10 MESA exam with a history of CVD events (atrial fibrillation, heart failure, and coronary heart disease [CHD]). Of the 2087 participants (68.7±9.1 years; 46% females), 153 had prior CVD events (78 atrial fibrillation, 25 heart failure, and 78 CHD). History of CVD events was associated with 18.5 ms higher liver native T1 ( P <0.001) and 1.4% greater ECV ( P =0.06). Prior atrial fibrillation was related to higher liver native T1 (β=21.1; P =0.001) and greater ECV (β=2.2; P =0.02), whereas previous heart failure was associated with greater liver ECV (β=4.1; P =0.02). There was also a relationship of prior CHD with liver native T1 (β=13; P =0.05) and ECV (β=1.9; P =0.05), which was attenuated by adjustment for coronary artery calcium score (β=7.1 and 1.6; P =0.37 and 0.13, respectively). Conclusions—: Liver fibrosis by T1-mapping magnetic resonance imaging is associated with history of heart failure, atrial fibrillation, and CHD in a multiethnic cohort. The association of liver fibrosis and CHD is at least in part mediated by atherosclerosis. Abstract : Supplemental Digital Content is available in the text.